Molecular Basis of White Adipose Tissue Remodeling That Precedes and Coincides With Hibernation in the Syrian Hamster, a Food-Storing Hibernator - Chayama, Yuichi; Ando, Lisa; Sato, Yuya; Shigenobu, Shuji; Anegawa, Daisuke; Fujimoto, Takayuki; Taii, Hiroki; Tamura, Yutaka; Miura, Masayuki; Yamaguchi, Yoshifumi (Frontiers in Physiology, 2019)
Mammalian hibernators store fat extensively in white adipose tissues (WATs) during pre-hibernation period to prepare for hibernation (HIB). However, the molecular mechanisms underlying the pre-hibernation remodeling of WAT have not been fully elucidated. Syrian hamsters, a food-storing hibernator, can hibernate when exposed to a winter-like short day photoperiod and cold ambient temperature (SD-Cold). Animals subjected to prolonged SD-Cold had smaller white adipocytes and beige-like cells within subcutaneous inguinal WAT (iWAT). Time-course analysis of gene expression with RNA-sequencing and quantitative PCR demonstrated that the mRNA expression of not only genes involved in lipid catabolism (lipolysis and beta-oxidation) but also lipid anabolism (lipogenesis and lipid desaturation) was simultaneously up-regulated prior to HIB onset in the animals. The enhanced capacity of both lipid catabolism and lipid anabolism during HIB is striking contrast to previous observations in fat-storing hibernators that only enhance catabolism during HIB. The mRNA expression of mTORC1 and PPAR signaling molecules increased, and pharmacological activation of PPARs indeed up-regulated lipid metabolism genes in iWAT explants from Syrian hamsters. These results suggest that the Syrian hamster rewires lipid metabolisms while preparing for hibernation to effectively utilize body fat and synthesize it from food intake during HIB.